Development of Land Cover and Carbon Storage in Plawangan Hill of Gunung Merapi National Park, Yogyakarta, Using Landsat Data Series 2009, 2013, 2017, and 2023 - Khan, Kamran; Sadono, Ronggo; Wilopo, Wahyu; Hermawan, Much. Taufik Tri (Institut Pertanian Bogor (IPB University), 2024)
Globally, habitat loss, deforestation, and climate change are mostly caused by land cover changes (LCC). The amount of land covered by trees has had a major impact on global warming and climate change. Increasing the amount of land cover helps to mitigate climate change and global warming. This study aims to investigate the changes in land cover and carbon storage in Plawangan Hill, Indonesia, over four years (2009, 2013, 2017, and 2023). The study site was defined as a conservation area that has been periodically impacted both directly and indirectly by volcanic eruptions. Images from Landsat 7 and 8 were used to collect data. Additionally, land cover changes were assessed using the forest canopy density (FCD Mapper) model, which was then utilized to quantify the carbon storage of the research site. The findings demonstrated fluctuations in land cover changes between 2009 and 2023. Additionally, changes in land cover have a direct impact on changes in carbon storage. The age of the trees, type of vegetation, succession stage, and history of eruptions were the variables that were apparent to be the main causes of these changes.